Terapi Keluarga Sebagai Intervensi Holistik Untuk Meningkatkan Kualitas Hidup Keluarga (FQOL) Pada Keluarga Dengan Anak Berberkebutuhan Khusus (ABK) - Bariyyah, Yayu Khoerul; Iskandar, Rizki Cahya; Rayanda, Resta; Aprilia, Imas Diana (Jurnal Ilmiah Global Education, 2025)
Families with children with special needs (CWSN) face unique and diverse challenges that affect not only the individual child but also the entire family structure. The emotional, psychological, and social strain borne by parents—especially mothers—often surpasses that experienced by families without CWSN. The Family Quality of Life (FQoL) paradigm serves as a crucial framework for understanding how families with CWSN evaluate their overall life satisfaction. Family therapy is increasingly recognized as a holistic intervention aimed at enhancing FQoL by focusing on the family unit as a whole. By improving communication, emotional well-being, and equitable distribution of caregiving responsibilities, family therapy has the potential to foster a more harmonious and enriched family atmosphere. This study aims to evaluate the effectiveness of family therapy in improving the FQoL of families with CWSN. Using a mixed-methods approach, data were collected through the FQoL scale questionnaire, in-depth interviews, and observations. The results show significant improvements in emotional well-being, family relationships, and social support dimensions following the intervention. These findings suggest that family therapy is a strategic intervention for creating a healthier and more empowered caregiving ecosystem and highlight the importance of implementing family therapy as a supportive intervention for families with CWSN, thereby enhancing their overall and integrative quality of life.